DEFICIENCY OF VITAMINS AND MINERALS DURING THE PREGNANCY - Usmonova Zarina Mukhtor kizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Pregnant women have an increased risk of hypovitaminosis due to their increased vitamin requirements. Hypovitaminoses of C, B6, B1 and folic acid are the most common. When prescribing vitamins, it should be remembered that these drugs can cause adverse events, and some of them have a potential teratogenic effect. Vitamins in complex multivitamin-mineral complexes may enter into ambiguous interactions with their other components. The more complex the composition of a vitamin preparation, the more difficult is the absorption of each vitamin separately and the more difficult it is to assess the positive and negative mutual influences of all components of the complex [6,7,8,9].